2007
DOI: 10.1051/vetres:2007031
|View full text |Cite
|
Sign up to set email alerts
|

A new concept to stimulate mucosal as well as systemic immunity by parenteral vaccination as applied to the development of a live attenuatedSalmonella entericaserovar Dublin vaccine

Abstract: -A new concept of slow "drip feeding" that enables activation of mucosal as well as systemic immunity following parenteral vaccination was demonstrated using Salmonella Dublin in a mouse model. The live vaccine candidate, N-RM25, generated from a wild S. Dublin strain utilising metabolic-drift (spontaneous chromosomal) mutations had a unique sensitivity to bile and restricted growth in the presence of a very low concentration of bile salts No. 3 (0.075% (w/v)) but also had the ability to survive in a high conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…The strain distribution analysis demonstrated that the bacteria had completely vanished from mouse organs at 14 days after vaccine immunization. These findings are consistent with a previous report (Mizuno et al ., ) in which that the vaccination strain was isolated from the heart, blood, liver and spleen of mice at 1 day after immunization and was eliminated at the end of the study. The results also showed that the inhibin gene vaccine had no effect on organ weights or histopathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…The strain distribution analysis demonstrated that the bacteria had completely vanished from mouse organs at 14 days after vaccine immunization. These findings are consistent with a previous report (Mizuno et al ., ) in which that the vaccination strain was isolated from the heart, blood, liver and spleen of mice at 1 day after immunization and was eliminated at the end of the study. The results also showed that the inhibin gene vaccine had no effect on organ weights or histopathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…N-RM25 was confirmed to be highly stable with no cross-resistance to ten different antimicrobials. Following parenteral vaccination of mice, N-RM25 was also confirmed to be safe and efficacious, inducing both significant serum and mucosal immune responses and protecting against homologous lethal challenge infection [27].…”
Section: Introductionmentioning
confidence: 92%
“…These results suggest that some factors, possibly mucosal immunity, contribute to the development of inflammatory reactions at the site. It was previously shown in a trial using mice that N-RM25 administered via the parenteral route induced significant mucosal immune responses in the gut 14 days post vaccination [27].…”
Section: Groupmentioning
confidence: 99%
See 2 more Smart Citations